A retrospective study on the efficacy and safety of bone cement in the treatment of endplate fractures - Zhao, Zhijian; Deng, Lei; Hua, Xi; Liu, Haojun; Zhang, Hao; Jia, Xuejun; Wei, Rushuai; Liu, Mingming; Lv, Nanning (Frontiers in Surgery, 2022)
kyphoplasty for spinal fracture. The purpose of this study is to investigate the effect of sealing endplate fracture with bone cement on minimally invasive treatment of spinal fracture. Methods: A total of 98 patients with osteoporotic vertebral fractures combined with endplate fractures treated with bone cement surgery in our hospital were retrospectively analyzed. They were grouped according to whether bone cement was involved in the endplate fractures. Group A: bone cement was not only distributed in the fractured vertebral body, but also dispersed into the endplate fractures. Group B: bone cement was confined to the fractured vertebra but did not diffuse into the cracks of the endplate. The basic information, imaging changes of the fractured vertebral body, VAS score, ODI score, bone cement distribution and postoperative complications of the two groups were analyzed and compared. Results: The height of the injured vertebra and the kyphotic Cobb angle in the two groups were significantly improved after surgery, but the anterior height of the vertebra in group B was lower than that in group A and the kyphotic Cobb angle was higher than that in group A at the last follow-up, the differences between the two groups were statistically significant (P<0.05). VAS score and ODI score in 2 groups were significantly improved after operation (P<0.05), but the VAS score and ODI score in group A were lower than those in group B at the last follow-up, and the difference between the two groups was statistically significant (P<0.05). The incidence of bone cement leakage and adjacent vertebral fracture in group A was higher than that in group B, and the difference was statistically significant (P<0.05). Conclusion: Diffusion of bone cement into the cracks of the endplate can effectively restore and maintain the height of the injured vertebra, relieve pain and restore lumbar function. However, diffusion of bone cement into the cracks of the endplate can increase the incidence of cement leakage and adjacent vertebral fractures.